Asthma prevalence among 16- to 18-year-old adolescents in Saudi Arabia using the ISAAC questionnaire - Al Ghobain Mohammed O; Al-Hajjaj Mohamad S; Al Moamary Mohamad S (BMC, 2012)
Abstract Background Most of the studies investigating the prevalence of asthma in various countries have focused on children below the age of 15 years or adults above the age of 18 years. There is limited knowledge concerning the prevalence of asthma in 16- to 18-year-old adolescents. Our objective was to study the prevalence of asthma and associated symptoms in 16- to 18-year-old adolescents in Saudi Arabia. Methods A cross-sectional study was conducted in secondary (high) schools in the city of Riyadh utilizing the International Study of Asthma and Allergies in Children (ISAAC) questionnaire tool. Results Out of 3073 students (1504 boys and 1569 girls), the prevalence of lifetime wheeze, wheeze during the past 12 months and physician-diagnosed asthma was 25.3%, 18.5% and 19.6%, respectively. The prevalence of exercise-induced wheezing and night coughing in the past 12 months was 20.2% and 25.7%, respectively. The prevalence of rhinitis symptoms in students with lifetime wheeze, physician-diagnosed asthma and exercise-induced wheeze was 61.1%, 59.9% and 57.4%, respectively. Rhinitis symptoms were significantly associated with lifetime wheeze (OR = 2.5, p value < 0.001), physician-diagnosed asthma (OR = 2.2, p < 0.001), and exercise-induced wheeze (OR = 1.9, p value < 0.001). Conclusions The prevalence of asthma and associated symptoms in 16- to 18-year-old adolescents in Saudi Arabia is high, although it is within range of reported prevalence rates from various parts of the world.